Histone Deacetylases in the Inflamed Intestinal Epithelium—Promises of New Therapeutic Strategies - Gerbeth, Lorenz; Glauben, Rainer (Frontiers in Medicine, 2021)
The intestinal epithelium is a complex, dynamic barrier that separates luminal contents from the immune compartment while mediating nutrient absorption and controlled passage of antigens to convey oral tolerance. A compromised epithelial barrier often leads to inflammation because immune cells in the lamina propria come into direct contact with luminal antigens. Defects in epithelial cell function were also shown to be involved in the etiology of inflammatory bowel diseases. These are severe, chronically relapsing inflammatory conditions of the gastrointestinal tract that also increase the risk of developing colorectal cancer. Despite major efforts of the scientific community, the precise causes and drivers of these conditions still remain largely obscured impeding the development of a permanent cure. Current therapeutic approaches mostly focus on alleviating symptoms by targeting immune cell signaling. The protein family of histone deacetylases (HDACs) has gained increasing attention over the last years, as HDAC inhibitors were shown to be potent tumor cell suppressors and also alleviate morbid inflammatory responses. Recent research continuously identifies new roles for specific HDACs suggesting that HDACs influence the cell signaling network from many different angles. This makes HDACs very interesting targets for therapeutic approaches but predicting effects after system manipulations can be difficult. In this review, we want to provide a comprehensive overview of current knowledge about the individual roles of HDACs in the intestinal epithelium to evaluate their therapeutic potential for inflammatory conditions of the gut.